Offering a Health Empowerment Program in a Faith-Based Community Clinic. Issue 3 (May 2021) - McGrane Minton, Heather; Lytle, Megan C.; Coleman, Renee; Briody, Sheila; Kristoffersen, Margaret; Sörensen, Silvia
Introduction . Given the excess burden of overweight/obesity in low-income communities, the objective of this pilot study was to examine the feasibility and effectiveness of a healthy living program (Health Empowerment Program) for improving physical activity, eating habits, and mental health outcomes. Adapted from the Diabetes Prevention Program (DPP), a 7-week biopsychosocial intervention that included spirituality was created.Methods . Participants (n = 153) recruited from a faith-based neighborhood health center were assessed using self-report measures for depressive and anxiety symptoms, self-regulation, physical activity, and eating habits at baseline, postintervention, and 3-month follow-up.Results . Participants had significant decreases in depressive symptoms ( β = −1.21; SE = 0.27; P < .001) and anxiety symptoms ( β = −0.69; SE = 0.24; P = .005) and significant increases in self-regulation ( β = 2.42; SE = 0.82; P = .003), time spent in physical activity ( β ; = 3.56; SE = 1.48; P = .016), and total healthy eating habits ( β = 0.97; SE = 0.16; P < .001).Conclusion. Although including spirituality in a healthy living program is feasible and is associated with improvements in outcomes, future research needs to consider how best to incorporate a modified DPP into community settings allowing access to all community members.